(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
The purpose of this work is to analyze the impact that the signing of a commercial negotiation or international treaty implies on the constitutional powers of Brazil. In the first part, the historical constitutional context is studied with special mention of the constituent process of this country, focusing on the changes that the transition from the dictatorship to a fully established democracy entailed. Subsequently, the constitutional social dimension and the incorporation of Brazil in Latin American integration are investigated, as well as the mechanisms for resolving commercial conflicts between countries. The international rise of Brazil through economic interactions is also addressed, analyzing its relationship with the European Union and the United States. This research aims to demonstrate that Brazil has actively participated in various integration processes, as well as in international organizations and forums, in order to develop and strengthen its presence abroad.